1952
DOI: 10.1002/jsfa.2740031206
|View full text |Cite
|
Sign up to set email alerts
|

The lignin fraction of animal feeding‐stuffs. III—The determination of ‘total lignin’

Abstract: The method proposed by the authors (see l'art I1 of this series) for the determination of ' acid-insolublc lignin ' excludes thc humin material which dissolvcs in 7 2 0 0 ( w i w ) sulphriric acid but is reprecipitated by dilution. Furthcr work has shown this huinin material t o possess thc propertics of lignin. Although i t is t o bc expected that thc ' acidinsoluble ' lignin will hc resistant to the digestive processes and its dctcrmination should *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1954
1954
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thus the lignin preparations isolated by the usual acid methods contain, besides the real hydrolysis residue, also substances dissolved by the strong acid but precipitated by the succeeding dilution. This fact was recognised by Paloheimo (14) and confirmed by Moon and Abou-Raya (12), who all considered also the precipitated fraction as lignin. Moon and Abou-Raya refer to their observation that the precipitate contains methoxyl and gives the color reaction of lignin.…”
mentioning
confidence: 58%
“…Thus the lignin preparations isolated by the usual acid methods contain, besides the real hydrolysis residue, also substances dissolved by the strong acid but precipitated by the succeeding dilution. This fact was recognised by Paloheimo (14) and confirmed by Moon and Abou-Raya (12), who all considered also the precipitated fraction as lignin. Moon and Abou-Raya refer to their observation that the precipitate contains methoxyl and gives the color reaction of lignin.…”
mentioning
confidence: 58%
“…The removal of protein has been accomplished also with enzymic digestion. One of the most frequently used enzymes is pepsin (7,15). Trypsin is also used (1), and in yet another method three proteolytic enzymes successively (6).…”
Section: Review Of Sulphuric Acid Methodsmentioning
confidence: 99%
“…Tarroni(25i) found that dried tomato waste could replace hay for fattening cattle. Interest in the composition and chemical characterization of lignin in grass and forages continues (258,259,260,261,262). The higher the crude fibre the lower was the milk yield.…”
Section: Movements Of Food In the Alimentary Tractmentioning
confidence: 99%